Inter and intrapatient evolution of hepatitis C virus - Di Lello, Federico Alejandro (2015)
Hepatitis C virus (HCV) has a short replication time, high mutation rates and large population sizes, all of which make it an excellent experimental model for evolution studies, because evolution can be visualized in real-time. In this review, we discuss the implications to study HCV evolution at the interpatient and intrapatient levels of infection. The HCV interpatient dynamics is relatively slow, because the generation time is generally long. Then, at population level, the HCV diversity originated by the high mutation and replication rates is modulated by the bottleneck at transmission. Thus, when the virus is transmitted to other hosts, viral diversity is reduced as a result of the founder effect. On the other hand, during intrapatient infection, HCV evolves rapidly, resulting in quasispecies. Accumulated evidence suggests that this quasispecies composition of the HCV population within the same individual may allow the virus to evade the immune response or escape treatment, leading to chronic infection. Thus, a better understanding of the complexities underlying the molecular evolution of HCV in natural populations is needed before accurate predictions of viral evolution can be made. In summary, HCV evolves both within and among patients. Consequently, HCV evolution should be studied at both levels in order to better understand the natural history of the virus and its potential implications in epidemiology, outcome of infection and progression of liver disease.